Spatiotemporal relationship characteristic of climate comfort of urban human settlement environment and population density in China - Zhang, Dahao; Zhou, Chunshan; Zhou, Yi; Zikirya, Bahram (Frontiers in Ecology and Evolution, 2022)
Rapid urbanization in China has brought about substantial changes in the urban climate, leading to accelerated shifts in the climate comfort of the human settlement environment. Additionally, in certain regions of China, a glaring disproportion exists in the distribution of population to the available area. Therefore, the climate comfort of such areas needs to be improved to enhance their habitability. In this study, we explored the spatiotemporal evolution characteristics of the climate comfort of the urban human settlement environment in China from 2000 to 2015, based on a three-level time scale of year, month, and day and using the temperature and humidity index and wind efficiency index. Additionally, the population density in China was calculated employing the population grid spatial calculation method. Subsequently, we compared and analyzed the spatiotemporal relationship characteristics between the climate comfort of the urban human settlement environment and population density. Our results indicated that (1) the extremely cold area was the largest, followed by the cold area, with the comfort area being the smallest. The area range of climate comfort and cold expanded northward, whereas the extremely cold area shrank from 2000 to 2015. (2) The duration of the comfort month and comfort day in southern China was higher than that in northern China. The climate comfort area of 3–4 months was the largest and that of 7–12 months the smallest, with the largest climate comfort area being 66–130 days, and the smallest 196–325 days. (3) The spatial difference in the climate comfort month was greater than the daily change, and the evolution process of various regions became relatively complex over time. The spatiotemporal evolution of the climate comfort day showed minimal change in the northwest, north, and northeast China, whereas it changed significantly in the southwest, south, central, and east China. These results imply that the population density in the country is generally concentrated in the climate comfort areas.